Venture Capital in China: Developing a Regulatory Framework - Vaughn, Christopher M. (Columbia Journal of Asian Law, 2003)
Venture capital first appeared in China in 1985, when the Chinese government released The Decision to Reform the Chinese Science and Technical System, its first official document addressing the topic. In Beijing that same year, the government sponsored China Venturetech Investment Corporation, China’s first ever venture capital firm, which specialized in high-tech venture investments and led the government’s formation of similar investment entities in other provinces around China. Yet the government, young to market economics and mired in ideological skepticism following Tiananmen Square, all but halted the nurturing of high-risk, high-return venture capital investments in 1989. China’s venture capital environment withered as a result. Nevertheless, the unpredictable game of private equity in China was underway. The 1990’s witnessed a volatile resurrection of the industry, and by the start of the 21 st century, venture capital in China had reached a new level of prominence. There are several explanations for venture capital’s newfound attractiveness. First, to the venture capitalist, China’s accession into the WTO means long-awaited liberalization in the investment field. China also has the world’s fastest growing and most closely watched Internet market and offers unprecedented governmental support in the high-tech field.” In light of Asia’s 1997 financial crisis, venture capital provides China with longer-term, non-speculative investment that supports innovation and skill transfer, elements not found in the portfolio-type investments of the 1997 financial debacle. At the same time, venture capital holds relief for China’s tightening credit market. Moreover, job growth associated with venture capital helps China stem its rising unemployment problems from sweeping state-owned enterprise reform. The venture capital formula suits not only the high-risks of investing in former state-owned entities and other entities deficient in market operating experiences, but also the government’s recent push to develop western China.